2016
DOI: 10.1017/s0033291716002403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early life stress on depression, cognitive performance and brain morphology

Abstract: Background Childhood early life stress (ELS) increases risk of adulthood Major Depressive Disorder (MDD) and is associated with altered brain structure and function. It is unclear whether specific ELSs affect depression risk, cognitive function and brain structure. Methods This cross-sectional study included 64 antidepressant-free depressed and 65 never depressed individuals. Both groups reported a range of ELSs on the Early Life Stress Questionnaire, completed neuropsychological testing and 3T MRI. Neuropsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
167
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(202 citation statements)
references
References 46 publications
15
167
1
5
Order By: Relevance
“…In terms of its pathogenesis, different reports had suggested that the environmental stresses to the genetically vulnerable individuals were attributed to the depression onset or relapse . Moreover, the evidence from many clinical trials showed that the early life stress could influence the neural development and lead to the deficiency in brain reward and cognitive circuits, subsequently resulting in the increased risk in depression . However, the cellular and molecular changes induced by adverse stressor leading to defect in the cognitive and emotional circuits have not yet elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of its pathogenesis, different reports had suggested that the environmental stresses to the genetically vulnerable individuals were attributed to the depression onset or relapse . Moreover, the evidence from many clinical trials showed that the early life stress could influence the neural development and lead to the deficiency in brain reward and cognitive circuits, subsequently resulting in the increased risk in depression . However, the cellular and molecular changes induced by adverse stressor leading to defect in the cognitive and emotional circuits have not yet elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Low SES also seems to be associated with developmental delay (specifically, a delay in cognitive development of executive functioning including working memory, inhibitory control, and cognitive flexibility), poor conduct, and callous behaviors [17,18,19]. These lead to consequences of transition to adulthood such that lower SES and early life stress influence both cognitive and associated neurobiological development, which are also associated with poor health outcomes in adulthood and comorbid metabolic and cardiovascular dysfunction [20,21]. Further, adverse living environment, may predispose to the development of characteristics and behaviors that are risk factors for multiple comorbidities, including obesity, smoking, and increased blood pressure trajectory, throughout adolescence into adulthood, and are further specifically associated with metabolic dysfunction and cardiovascular disease in adulthood [10,22,23,24].…”
Section: Aces and Traumamentioning
confidence: 99%
“…Further, there may be neurobiological underpinnings to the buffering effect of resilience on ACEs. Though ACEs have been associated with neurocognitive impairment, trait resilience is associated with better neurocognitive skills such as non-verbal memory [20,21,97]. Importantly, a limitation to exploring this concept is the assessment of resilience, which in research investigations is done by collecting data on related concepts such as perseverance and self-confidence as assessed by the Connor-Davidson-Resilience Scale (CD-RISC) questionnaire, or other concepts measures like coping, social support, emotional and behavioral reactivity, and compassion [98,99].…”
Section: Mindfulnessmentioning
confidence: 99%
“…However, it is unclear whether the promising results for CBASP can only be achieved for the subgroup of patients with early-onset, chronic depressive disorder and a history of early adverse events, or for all types of depressed patients. Many features that are considered crucial for CBASP interventions (such as early adverse life events, insecure attachment styles) are also prevalent in episodic depression and even in nondepressed controls [13]. Therefore CBASP could be beneficial for nonchronic subtypes as well, which has never been tested before.…”
Section: Introductionmentioning
confidence: 99%